The effect of race on survival after local therapy in metastatic prostate cancer patients - Mazzone, Elio; Bandini, Marco; Preisser, Felix; Nazzani, Sebastiano; Tian, Zhe; Abdollah, Firas; Soulieres, Denis; Graefen, Markus; Montorsi, Francesco; Shariat, Shahrokh; Saad, Fred; Briganti, Alberto; et al. (Canadian Urological Association Journal, 2018)
Introduction: Local therapy (LT) may offer a survival advantage in highly select, newly diagnosed metastatic prostate cancer (mPCa) patients. However, it is unknown whether the benefits vary in Caucasian vs. African American (AA) patients. Methods: Within the Surveillance Epidemiology and End Results (SEER) database (2004–2014), we focused on Caucasians and AA patients with newly diagnosed mPCa treated with LT: radical prostatectomy (RP) and brachytherapy (RT). Endpoints consisted of cancer-specific mortality (CSM) and overall mortality (OM). Kaplan-Meier analyses and multivariable Cox regression models tested for racial difference in CSM and OM. Results: Between 2004 and 2014, we identified 408 (77.2%) Caucasians and 121 (22.8%) AAs with newly diagnosed mPCa treated with LT: RP (n=357) or RT (n=172). According to race, when LT is defined as RP, Caucasian patients had a significantly longer survival vs. AA patients: CSM-free survival 123 vs. 63 months (p=0.004) and OM-free survival 108 vs. 46 months (p=0.002). The CSM and OM benefits were confirmed in multivariable analyses (hazard ratio [HR] 0.56, p=0.01 for CSM; HR 0.60, p=0.01 for OM). However, no differences in CSM or OM were recorded according to race when LT consisted of RT. Conclusions: Our results indicate that race is not associated with difference in survival after LT in mPCa patients. However, when focusing on RP-treated patients, Caucasian race is associated with higher CSM and OM rates relative to AA race. This racial difference does not apply to RT. Our findings should be considered in future prospective trials for the purpose of preplanned stratification according to race.